Hommage à Yourcenar : une réflexion écologique d’avant-garde - Chehab, May (Σύγκριση/Comparaison/Comparison, 2018)
Our attention in this study focuses on Marguerite Yourcenar’s (1903-1987) ecological reflection. Firmly engraved in her literary work, it is also to be found in various speeches, contributions to collective works, and in an early activism that goes beyond a purely intellectual environmentalism. In a word, the ecological issue haunts Yourcenar to the highest point, until the last year of her life ‒and even beyond.